(untitled) (Research, Society and Development, 2022)
Cancer is characterized by the disordered growth of cells, which may invade adjacent tissues or organs at a distance. The treatment of this pathology has several adverse reactions, among them the loss and weight gain. In view of this, kinesiotherapy becomes extremely important for women with this diagnosis, since it is a physiotherapeutic approach which consists in the use of movement as therapy, being an indispensable tool for reestablishing the function of limbs and movements. To analyze whether there is an association between nutritional management and kinesiotherapy in weight management. This is an integrative literature review, with a search conducted from May to June, 2022. To select the articles, searches were performed in the main databases BVS (Virtual Health Library) and PubMed (National Library of Medicine), the latter with free access to MEDLINE database. It was observed that many women with breast cancer are unaware of the side effects of treatment and are not guided to seek physiotherapy, which delays their rehabilitation. However, studies show that the monitoring and development of training with exercises designed by the physiotherapist contributes to the improvement of muscle strength to perform daily tasks as well as self-esteem and confidence, thus improving the quality of life and helping in weight maintenance. It is notable the importance of physical activity contributing to improving the quality of life of patients with breast cancer, reducing their risk and improving the prognosis.